Fractional Integral Inequalities of Hermite–Hadamard Type for Differentiable Generalized h-Convex Functions - Yingxia Yang; Muhammad Shoaib Saleem; Mamoona Ghafoor; Muhammad Imran Qureshi (Journal of Mathematics)
In the present paper, some fractional integral inequalities of Hermite–Hadamard type for functions whose derivatives are generalized h-convex are established. Moreover, several particular cases are also discussed which can be deduced from our results. As special cases, one can obtain several new versions of the results of generalized h-convexity for other various generalizations of convex functions.